Effect of Virtual Reality on Stress Reduction and Change of Physiological Parameters Including Heart Rate Variability in People With High Stress: An Open Randomized Crossover Trial - Kim, Hyewon; Kim, Dong Jun; Kim, Seonwoo; Chung, Won Ho; Park, Kyung-Ah; Kim, James D. K.; Kim, Dowan; Kim, Min Ji; Kim, Kiwon; Jeon, Hong Jin (Frontiers in Psychiatry, 2021)
Introduction: Although attempts to apply virtual reality (VR) in mental health care are rapidly increasing, it is still unclear whether VR relaxation can reduce stress more than conventional biofeedback does. Methods: Participants consisted of 83 healthy adult volunteers with high stress, which was defined as a score of 20 or more on the Perceived Stress Scale-10 (PSS-10). This study used an open, randomized, cross-over design with baseline, stress, and relaxation phases. During the stress phase, participants experienced the intentionally generated shaking VR and serial-7 subtraction. For relaxation session, participants underwent the relaxation session as randomly assigned on day1, and the other type of relaxation session was applied on day 2. We compared the State-Trait Anxiety Inventory-X1, X2 (STAI-X1, X2), the Numeric Rating Scale (NRS), and physiological parameters including heart rate variability (HRV) indexes in the stress and relaxation phases. Results: A total of 74 participants were included in the analyses. The median age of participants was 39 years, STAI-X-1 was 47.27 (SD = 9.92), and NRS was 55.51 (SD = 24.48) at baseline. VR and biofeedback significantly decreased STAI-X-1 and NRS from the stress phase to the relaxation session, while the difference of effect between VR and biofeedback was not significant. However, there was a significant difference in electromyography, LF/HF ratio, LF total and NN50 between VR relaxation and biofeedback. Conclusion: VR relaxation was effective in reducing subjectively reported stress in individuals with high stress.